Art practice as research inquiry in the visual arts - Sullivan, Graeme 1951- (Thousand Oaks, California Sage Publications, Inc., 2005)
"Art Practice as Research: Inquiry in the Visual Arts presents a compelling argument that the creative and cultural inquiry undertaken by artists is a form of research. The text explores themes, practices, and contexts of artistic inquiry, positioning them within the discourse of research." "Art Practice as Research is perfectly suited as a text for courses in art education, the visual arts, research methods in art education, as well as general research methods courses in education and the humanities. This will also be an invaluable reference for anyone with an interest in interdisciplinary research in the social sciences and the role of imaginative inquiry in human understanding."--Jacket.
Introduction: Reviewing Visual Arts Research -- Changing Demands of Visual Arts Theory and Practice -- Limitations of Current Visual Research Methodologies -- Art as Practice as Research -- Strategies for Using Art Practice as Research -- Contexts for Visual Arts Research -- Pigment to Pixel -- The Enlightenment as a Research Project -- Promise of Project -- Fractured Realities -- Paradigms Lost -- Method as Truth -- Doubting Doctrines -- Theorizing Visual Arts Practice -- Explanation, Understanding and Beyond -- Probability, Plausibility and Possibility -- Theorizing in Practice -- Theorizing Visual Arts as Practice-Based Research -- Theorizing Art Practice as Transformative Research -- Visual Arts Research Practices -- Visual Knowing -- Visual Cognition -- Thinking Practices in the Visual Arts -- Visual Arts Knowing: A Framework -- Visual Art as Transcognitive Practice -- A Case Study: Critical Influence -- Artist as Theorist -- Sites of Practice -- Re-Emergence of the Artist-Theorist -- Visual Arts Research Practices -- Practice as Theory -- A Framework for Visual Arts Research Projects -- Visual Practice: Experiences -- Empirical Inquiry: Exercises -- Interpretive Discourse: Encounters -- Critical Process: Enactments -- Conclusion -- Epilogue: Conclusions and Beginnings.
Includes bibliographical references (pages 227-244) and index.
Keywords: Art -- Research; Art -- Study and teaching